Questioning China’s Peaceful Development: A Mahanian Sea Power Analysis of Blue Water Navy Accumulation - Patricia, Patricia; Satya, Putu Agung Nara I.P. (UI Scholars Hub, 2022)
China has been rapidly accumulating naval capabilities for nearly 4 decades with the ambition of pursuing blue-water-navy forces through its People’s Liberation Army Navy (PLAN). With its peaceful development policy, the acquisition of such powers has been interpreted as an anomaly and therefore resulted in an increase of security dilemmas between states. In the quest for explanations behind China’s actions, multiple scholars have examined this phenomenon by utilizing offensive realism, defensive realism, and Tirpitzian non-hegemonic naval theory. Thus, this paper brings another perspective by applying the Mahanian Sea Power approach. Consequently, the analysis established that China’s pursuit of blue-water-navy is driven by its interest in economic supremacy. In addition, the intention is also influenced by its wide coastline, large population, competitive nationals, and independent decisive government. The paper concludes that a blue-water-navy is a necessity for China in order to access markets, secure territorial interests, and obtain command of the sea for economic purposes.